A Visual Aid and Objective Rule Encompassing the Data Features of Visual Analysis - Manolov, Rumen; Vannest, Kimberly J. (Behavior modification, 2023)
Visual analysis of single-case research is commonly described as a gold standard, but it is often unreliable. Thus, an objective tool for applying visual analysis is necessary, as an alternative to the Conservative Dual Criterion, which presents some drawbacks. The proposed free web-based tool enables assessing change in trend and level between two adjacent phases, while taking data variability into account. The application of the tool results in (a) a dichotomous decision regarding the presence or absence of an immediate effect, a progressive or delayed effect, or an overall effect and (b) a quantification of overlap. The proposal is evaluated by applying it to both real and simulated data, obtaining favorable results. The visual aid and the objective rules are expected to make visual analysis more consistent, but they are not intended as a substitute for the analysts’ judgment, as a formal test of statistical significance, or as a tool for assessing social validity.